An Efficient One-Pot Synthesis of 1,8-Dioxodecahydroacridines Using Silica-Supported Polyphosphoric Acid (PPA-SiO2) under Solvent-Free Conditions - Farid Moeinpour; Amir Khojastehnezhad (E-Journal of Chemistry)
Silica gel–supported polyphosphoric acid (PPA-SiO2) was found to be an efficient catalyst for the synthesis of 1,8-dioxodecahydroacridines via one-pot three-component condensation of aryl aldehydes, dimedone, and ammonium acetate or 4-methyl aniline in high yields, easy workup procedure and short period of times. The catalyst was separated by simple filtration and used in the reaction three times without any significant loss of its activity.